Reinterpretasi Relasi Tuhan dan Manusia Syed Muhammad Naquib Al-Attas - Tri Arwani Maulidah (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2018)
The article attempts to reanalyze the concept of God, human, and their relation. God, in Islam, is The One, The Life, The Eternal, and The Endless. His Oneness is absolute, but His Absoluteness is unlike the absoluteness of the universe. God is transcendent and immanent at the same time. Al-Attas distinguishes the concept of God as Rabb and God as IlÄh. Human, to al-Attas, is spirit and organism, and body and soul. The organismic side of human beings along with their five senses functions to help them living in the world. The spiritual dimension of human beings, on the other side, has an ability to formulate a set of meanings which involve assessment, differentiation, and explanation. When we observe the relation of God and human from the concept of tawá¸¥Ä«d ulÅ«hÄ«yah and tawá¸¥Ä«d rubÅ«bÄ«yah we will find two interrelated role of human, namely the role as Godâ€™s servant and the role as Godâ€™s representative and mandate (khalÄ«fah) on the earth. These two roles are inseparable. Al-Attas argues that separation of the two will create imbalance personality of the human. It will subsequently jeopardize their existence and the earth they live on.